2014
DOI: 10.1186/2052-336x-12-30
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between benthic macroinvertebrate bio-indices and physicochemical parameters of water: a tool for water resources managers

Abstract: The ecosystem health of rivers downstream of dams is among the issues that has become focus of attention of many researchers particularly in the recent years. This paper aims to deal with the question, how the environmental health of a river ecosystem can be addressed in water resources planning and management studies. In this study, different parameters affecting the ecosystem of river-reservoir systems, as well as various biological components of river ecosystems have been studied and among them, benthic mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The BMWPL index value was high for less polluted sites, for example, and low for highly polluted sites. Similar results were previously reported for different lentic ecosystems elsewhere (Rashid & Pandit, ; Yazdian, Jaafarzadeh, & Zahraie, ) and Ethiopia (Gezie et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…The BMWPL index value was high for less polluted sites, for example, and low for highly polluted sites. Similar results were previously reported for different lentic ecosystems elsewhere (Rashid & Pandit, ; Yazdian, Jaafarzadeh, & Zahraie, ) and Ethiopia (Gezie et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…According to Sabater (), the hydrological regime (dry seasons alternating with high water seasons or floods) of Mediterranean rivers favours benthos organisms more and leads to a poverty of the true plankters, because these systems are unstable. The most commonly used macroinvertebrate indices in river evaluation include species richness, evenness, diversity, and dominance indices, biological monitoring working party, Average Score per Taxon, and the total number of Ephemeroptera, Plecoptera, and Trichopteraindex (Yazdian, Jaafarzadeh, & Zahraie, ). These indices lack the inclusion of specific physicochemical parameters related to eutrophication as in the case of the EISR.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008 a study revealed that these river-bed organisms have special features which makes them suitable to environmental and pollution studies such as varying degrees of tolerance to different environmental elements, another feature revealed that these organisms moves very little and very slow within their local confines, has a long life span and is very useful in the food chain (15). The composition of these Benthic Invertebrates is effected by the physical and chemical features of the particular Wetland or Lake such as the nature of the river bed, depth, the degree of heat, the quantity of Hydrogen and Oxygen absorbed as well as the level of pollution (50). One of the major impacts that affect rivers is the pollution of their waters by both domestic and industrial waste (10), which endangers the life of not only plants and animal but also human health (27).…”
Section: Introductionmentioning
confidence: 99%